KAJIAN SOSIOLOGIS SASTRA DAN MASYARAKAT DALAM NOVEL TUHAN IZINKAN AKU JADI PELACUR KARYA MUHIDIN M DAHLAN SEBAGAI KAJIAN DIDAKTIS - Via Nugraha; Woro Wuryani (Jurnal Semantik, 2021)
Sociological study of literature is an analysis of literary works using a sociological approach to see therelationship between Tuhan Izinkan Aku Menjadi Pelacur TIAMP's novel work and realistic facts orfacts contained in the TIAMP novel, where literature is part of the description of the realities of sociallife. Literature will die without the presence of people that exist in literature. The author of the novelis an author who is also a member of society. In the story, the literary work presents the social realityof life that occurs in society in a story with a few economic, social, political, cultural, artistic andother problems. Of course, it contains the noble values of culture if we examine more deeply. In thisstudy, the researcher will examine the study of literature and society that touches the problems ofliterature and society in the political, economic, religious, and social aspects contained in the facts ofthe story in the novel and will describe the influence of society on problems in the TIAMP novel seenfrom the economic, political aspects. , religion, and social and from the analysis of the novel carriedout a parameterized assessment of the didactic study, so that the dictatorship of the TIAMP novel wasillustrated. The research method used was descriptive qualitative. The researcher will describe thefacts of the story in the novel related to problems in the economic, religious, and social aspects andthe people's perspective in solving the problems in the novel Lord Let Me Be a Pelacur. The results ofthis study can find the intertwined relationship between literature and society sociologically in termsof economic, social, and religious aspects.